The Relevance of Pancasila as the Basis for the Development of Participant Civic Culture towards Millennial Generation - Perdana, Maqfira Wahyu; Marzuki, Marzuki (International Conference on Multidisciplinary Research, 2020)
This study aims to describe the relevance of Pancasila as the basis for the development of participantcivic culture towards the millennial generation. This research is qualitative research with a phenomenology research design. The subject of this study consisted of Civic Education teachers,community personage, political observers, members of the Pancasila Lovers Community, and membersof a youth organization in Kediri City, East Java. In-depth interviews and documentation were used asdata collection techniques. The data were then analyzed by using the interactive analysis modeldeveloped by Miles and Huberman. The results of this study showed that Pancasila is still perceived asthe basis for the development of the participant civic culture of the Indonesian millennial generationuntil today. This can be seen from the attitudes and actions of the millennial generation that reflect thefive principles of Pancasila, both at schools and in the community. The relevance of Pancasila as thebasis in developing the awareness and the political participation among the millennial generation can beseen from the Civic Education learning carried out by teachers at school. Meanwhile, in the community,this can be seen from the activities that they are involved in, such as expressing their aspiration, voting,engaging in public discussions and in some organizations. Through these activities, it is expected thatPancasila will stay relevant to the future Indonesian generation and be able to induce high participationand patriotism among them. Keywords: Pancasila, Civic Culture, Millennial Generation.